The efficacy of somatostatin treatment in bleeding oesophageal varices - Kadir AKSÖZ,; Nafi YAZICIOĞLU,; Belkıs ÜNSAL,; Uğur GÖNENÇ,; Ali ERGİN,; Günay ÖNDER,; Himmet KARACA,; Sadun KOŞAY, (Turkish Journal of Gastroenterology, 2020)
-